Analisis Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan pada Sektor Perusahaan Manufaktur akan Terdaftar di BEI 2018-2022 - Syarifa Melya Ningsih; Nini Sumarni (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research is motivated by the existence of fraudulent financial reporting that occurred in several industrial sectors in companies in Indonesia. This research aims to determine the influence of the pentagon fraud theory in detecting fraudulent financial statements in the manufacturing company sector, Food and Beverage sub-sector on the 2018-IDX. 2022. A sample of 12 companies was obtained with a total sample size of 60 sample data. The data used is secondary data in the form of financial reports on food and beverage sector manufacturing companies listed on the IDX 2018-2022. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear regression test, hypothesis test which is processed using the IBM SPSS 22 application. Based on the research results which show that the ACHANGE value is obtained, tTable is 2.015. Because tcount is greater than ttable, namely -2.501 ≥ -2.015 and the significance value (Sig.) ≤ 0.05, the LEV value obtained is tTable 2.356. Because the tcount is greater than the ttable, namely 2.356 ≥ 2.015 and the significance value (Sig.) ≤ 0.05, the ROA value is obtained tTable 2.015 because the tcount is greater than the ttable, namely 0.179 ≤2.015 and the significant value is ≥ 0.05 and the INVENTORY value obtained is tTable 2.015. Because tcount is greater than ttable, namely -2.908 ≥ -2.015 and the significance value (Sig.) ≤ 0.5 and the BDOUT value, we get tTable 2.015. Because tcount is smaller than ttable, namely -0.452 ≤ -2.015 and significance value (Sig.) ≤ 0.05